Rethinking the neurological examination I: static balance assessment - Péricles A. Maranhão-Filho; Eliana Teixeira Maranhão; Marcos Martins da Silva; Marco Antônio Lima (Arquivos de Neuro-Psiquiatria)
The authors advocate a modernization of the neurologic exam with regard to the evaluation of static equilibrium through the application of some easily performed and interpreted bedside maneuvers like the Clinical Test of Sensory Integration and Balance - modified and the Functional Reach Test. The authors also believe that these and other assessments, such as that of the risk of falling for elderly patients, should be incorporated into the routine neurological examination.